Economic Efficiency and Legal Certainty in Indonesia’s Downstream Mining Policy - Muhammad Agus Subandi (The Indonesian Journal of Economic Analysis of Law, 2026)
Indonesia’s downstream mining policy has emerged as a strategic instrument to increase domestic value-added, promote industrialization, and strengthen national economic resilience. However, the implementation of this policy raises important questions regarding economic efficiency and legal certainty for investors and business actors. This study examines the interaction between economic objectives and legal frameworks governing mineral downstreaming in Indonesia. Using a normative legal approach combined with economic analysis of law, the research evaluates whether existing regulations create efficient incentives while maintaining predictable legal environments. The findings indicate that downstream mining policies generate significant economic benefits through increased investment, employment opportunities, and export diversification. Nevertheless, regulatory inconsistencies, frequent policy changes, and overlapping institutional authorities have contributed to legal uncertainty, increasing transaction costs and reducing investor confidence. From an economic perspective, legal certainty functions as a critical prerequisite for efficient resource allocation and long-term industrial development. The study argues that the effectiveness of downstream mining policies depends not only on protectionist measures but also on coherent regulatory design, transparent governance, and stable enforcement mechanisms. Furthermore, balancing state control over natural resources with market efficiency remains essential for achieving sustainable economic outcomes. The research concludes that strengthening regulatory consistency and institutional coordination can enhance both economic efficiency and legal certainty, thereby supporting Indonesia’s broader industrial transformation agenda. These findings contribute to the growing literature on economic analysis of law by demonstrating how legal institutions influence economic performance in resource-based sectors.